Autoimmune paraneoplastic syndromes associated to lung cancer: A systematic review of the literature Part 4: Neurological paraneoplastic syndromes, involving the peripheral nervous system and the neuromuscular junction and muscles. (September 2017) - Ruelle, Lucien; Bentea, Georgiana; Sideris, Spyridon; El Koulali, Mohamed; Holbrechts, Stéphane; Lafitte, Jean-Jacques; Grigoriu, Bogdan; Sculier, Claudine; Meert, Anne-Pascale; Durieux, Valérie; Berghmans, Thierry; Sculier, Jean-Paul
Abstract: The development of new immune treatment in oncology and particularly for lung cancer may induce new complications, particularly activation or reactivation of auto-immune diseases. In this context, a systematic review on the auto-immune paraneoplastic syndromes that can complicate lung cancer appears useful. This article is the fourth of a series of five and deals mainly with neurological paraneoplastic syndromes involving the peripheral nervous system and the neuromuscular junction and muscles.